Systematic Literature Review: Implementasi Pembelajaran STEAM pada Pendidikan Dasar di Indonesia Tahun 2021–2026 - Mujayanti, Isnaeni; Rohimah, Iyoh; Alawiah, Tuti; Supriyadi; Surani, Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach represents a pivotal pedagogical innovation for equipping elementary school students with 21st-century skills within the Merdeka Curriculum framework. This study aims to comprehensively analyze publication trends, implementation patterns, field barriers, and the effectiveness of the STEAM approach in Indonesian primary education from 2021 to 2026. The methodology employed is a Systematic Literature Review (SLR), adopting the PRISMA protocol and SALSA framework to synthesize 30 relevant scientific journal articles. The findings reveal a chronological shift in research focus, transitioning from post-pandemic motivation enhancement to structural co-curricular (P5) integration in the Merdeka Curriculum, and recently advancing toward sophisticated digitalization using immersive technologies (Metaverse and Augmented Reality). However, the geographical distribution of publications remains highly skewed toward urban areas in Java Island. Classroom implementation is predominantly driven by three macro models: Project-Based Learning (PjBL-STEAM), the RADEC model, and virtual media utilization. Key systemic barriers identified include a sharp urban-rural technological infrastructure gap, teachers' limited pedagogical competence in balancing engineering and mathematics components, and complex assessment administration. Despite these challenges, STEAM integration proves highly effective in fostering Higher-Order Thinking Skills (HOTS), enhancing creativity via the arts component, and cultivating collaborative as well as socio-cognitive skills, serving as an essential foundation for the Indonesia Emas 2045 vision.